HUBUNGAN DUKUNGAN SOSIAL SUAMI DENGAN TINGKAT KECEMASAN IBU PRE MENOPAUSE DI DUSUN WONOKERTO DESA WONOKERTO KECAMATAN KEDUNGGALAR NGAWI - Tunjung Sri Yulianti; Endang Dwi Ningsih; Ahmad Nur Kholik (KOSALA : Jurnal Ilmu Kesehatan, 2014)
Abstract The background of this research is that women will enter menopause usually will experience physical and psychological changes that will cause anxiety. With the social support from her husband will make her feelings become calm, and feel cared for so as to reduce the anxiety. The results of a preliminary survey data obtained 2 of 4 pre-menopausal women say feel anxious, feel a lot of diseases that can attack the body after their menopause, feeling old, wrinkled and no longer pretty scared of her husband so they could later turn to other women. The purpose of this study was to determine the relationship of husband’s social support to pre menopausal women’s anxiety levels at Hamlet Village Wonokerto Wonokerto Kedunggalar Ngawi subdistrict. The subject of this study are all pre-menopausal women in Hamlet Village Wonokerto Wonokerto District of Kedunggalar Ngawi totaling 20 people by using total sampling techniques. Methods of data collection in this study conducted by interview and observation then analyzed with Chi Square with a significant level of p: 0.05. The results of this study are the husband's social support included in optimal category and pre menopausal women’s anxiety levels included in the category of no anxiety. Analysis with Chi Square test with p = 0.05, obtained 0,031 results (probability <0.05). The conclusion of this study is that there is a significant relationship between husband’s social support with pre menopausal women’s anxiety levels at Hamlet Village Wonokerto Wonokerto Kedunggalar Ngawi subdistrict. Keywords: Menopause, Anxiety, Social Support